Linking dietary intake, circadian biomarkers, and clock genes on obesity: A study protocol - Lages, Marlene; Barros, Renata; Carmo-Silva, Sara; Guarino, Maria P. (Frontiers in Nutrition, 2023)
Background The prevalence of obesity continues to rise, and although this is a complex disease, the screening is made simply with the value of the Body Mass Index. This index only considers weight and height, being limited in portraying the multiple existing obesity phenotypes. The characterization of the chronotype and circadian system as an innovative phenotype of a patient’s form of obesity is gaining increasing importance for the development of novel and pinpointed nutritional interventions. Objective The present study is a prospective observational controlled study conducted in Portugal, aiming to characterize the chronotype and determine its relation to the phenotype and dietary patterns of patients with obesity and healthy participants. Methods Adults with obesity (study group) and healthy adults (control group), aged between 18 and 75, will be enrolled in this study. Data will be collected to characterize the chronotype, dietary intake, and sleep quality through validated questionnaires. Body composition will also be assessed, and blood samples will be collected to quantify circadian and metabolic biomarkers. Discussion This study is expected to contribute to a better understanding of the impact of obesity and dietary intake on circadian biomarkers and, therefore, increase scientific evidence to help future therapeutic interventions based on chronobiology, with a particular focus on nutritional interventions.